Investigative Teaching Sequence Contextualized with Diabetes Mellitus - Magalhaes, Prislaine Pupolin [UNESP]; Oliveira, Rodrigo Cardoso de; Iano, Flavia Godoy [UNESP]; Ferraz, Isabela Pereira [UNESP]; Zuliani, Silvia Regina Quijadas Aro [UNESP] (Soc Brasileira Bioquimica & Biologia Molecular, 2022)
Problem-Based Learning (PBL) and Investigative Teaching Sequences (SEI) seek to help and encourage the construction of knowledge, where the student is the protagonist in an activate learning. This article presents the insertion of a contextualized and interdisciplinary SEI within a curriculum based on PBL. An activity contemplates and integrates basic and clinical concepts. The SEI was previously tested and validated in a Medicine course at a Public University, using Diabetes mellitus as a problematization and context. SEI by a well-constituted sequence of actions. Appropriate to the problem, the group's students raise hypotheses, and develop an experimental activity with the materials and apparatus available. Supervised by the teacher, as experimental tests, followed by analysis and argumentation obtained, which were discussed and presented by the groups in the form of conceptual maps. The students thought in an innovative and fruitful way, highlighting the importance of establishing relationships between theorists and experimenting with the basic and critical proposal.
Keywords: Experimental Investigative Activities; Diabetes Mellitus; Experimental Biochemistry